Immune profiling identifies CD8+ T-cell subset signatures as prognostic markers for recurrence in papillary thyroid cancer - Chen, Zhen; Guo, Meng-Li; Li, Ya-Yi; Yan, Kai; Li, Liang; Shen, Fei; Guan, Haixia; Liu, Qing-Zhi; Xu, Bo; Lian, Zhe-Xiong (Frontiers in Immunology, 2022)
Background: Thyroid tissue has a special immune microenvironment that is not well characterized. Whether immune cells have a prognostic value in the recurrence of papillary thyroid cancer (PTC) needs further investigation. Methods: Multinodular non-toxic goiter (MNG) was taken as normal tissue for the difficulty in obtaining completely normal thyroid tissue (normal thyroid function, no thyroiditis, and no nodules). We compared the composition of mononuclear cells (MNCs) in peripheral blood and thyroid tissues from MNG and PTC patients by high-dimensional flow cytometry profiling and verified the results by multiplex immunohistochemistry. The recurrence rates of PTC patients with different CD8+T cell subset signatures were compared using TCGA database. Results: We observed that the immune cell composition of MNG was different from that in peripheral blood. Thyroid tissue contains higher percentages of T cells and NK cells. Moreover, the percentages of memory T cells and Treg cells were higher in thyroid than peripheral blood, and increased in PTC tumors. We further focused on the anti-tumoral CD8+T cells, and found that the expression patterns of PD-1, CD39, and CD103 on CD8+T cells were different between MNG and PTC. Importantly, we found higher percentages of PD-1+CD39+CD103+CD8+T and PD-1+CD39+CD103-CD8+T cells in PTC tumor tissues from recurrent patients than non-recurrent patients. By analyzing PTC data from TCGA database, we found the expression patterns of these molecules were associated with different pathologic types and genders among PTC patients. Moreover, patients with PD-1hiCD39loCD103hiCD8hi, PD-1hiCD39hiCD103loCD8hi and PD-1loCD39hiCD103hiCD8hi expression patterns have a higher 10-year recurrence-free survival. Conclusion: The immune microenvironment in MNG tissue is distinct from that in peripheral blood and paratumor tissue. More memory CD8+T cells were detected in PTC, and expression patterns of PD-1, CD39 and CD103 on CD8+T cells were significantly different in physiological and gender and associated with recurrence rate of PTC. These observations indicate that CD8+T cell signatures may be useful prognostic markers for PTC recurrence.